Optimizing the Personalized Care for the Management of Rectal Cancer: A Consensus Statement - Aytaç, Erman; Özer, Leyla; Baca, Bilgi; Balık, Emre; Kapran, Yersu; Taşkın, Orhun Cığ; Oyan Uluç, Başak; Abacıoğlu, Mehmet Ufuk; Gönenç, Murat; Bölükbaşı, Yasemin; Çil, Barbaros E.; Baran, Bülent; et al. (Turkish Journal of Gastroenterology, 2022)
Colorectal cancer is the third most common cancer in Turkey. The current guidelines do not provide sufficient information to cover all aspects of the management of rectal cancer. Although treatment has been standardized in terms of the basic principles of neoadjuvant, surgical, and adjuvant therapy, uncertainties in the management of rectal cancer may lead to significant differences in clinical practice. In order to clarify these uncertainties, a consensus program was constructed with the participation of the physicians from the Acıbadem Mehmet Ali Aydınlar and Koç Universities. This program included the physicians from the departments of general surgery, gastroenterology, pathology, radiology, nuclear medicine, medical oncology, radiation oncology, and medical genetics. The gray zones in the management of rectal cancer were determined by reviewing the evidence-based data and current guidelines before the meeting. Topics to be discussed consisted of diagnosis, staging, surgical treatment for the primary disease, use of neoadjuvant and adjuvant treatment, management of recurrent disease, screening, follow-up, and genetic counseling. All those topics were discussed under supervision of a presenter and a chair with active participation of related physicians. The consensus text was structured by centralizing the decisions based on the existing data. Cite this article as: Aytaç E, Özer L, Baca B, et al. Optimizing the personalized care for the management of rectal cancer: A consensus statement. Turk J Gastroenterol. 2022;33(8):627-663.